Coral reef fish abundance and diversity of seagrass beds in Kavaratti atoll, Lakshadweep, India - Vijayanand, P E; Pillai, N G K (Indian Journal of Fisheries, 2011)
The community organization of coral reef fishes in the seagrass sub-habitat of Kavaratti toll, Lakshadweep, India was studied during the period from January 1991 to June 1992. Twenty-seven families represented by 65 species were recorded by the visual censes method. The community diversity for families and species was 2.49 and 3.14 respectively. Juveniles and sub-adults of the most adult reef fish, which inhabit other sub-habitats, were recorded here. The high species diversity in the seagrass beds is due to their roles as nurseries, shelter and foraging grounds for many species. Labridae, Chaetodontidae, Acanthuridae and Mullidae were the most speciose families. Ocurrence of siganids was highly seasonal. The cover that seagrass canopy provides conceals many species and perhaps influenced counts. The occurrence of balistids could be related to the presence of interstitial and patches and abundant invertebrate food. Scorpaenids subsisted on abundant invertebrates and juveniles fishes. High counts and pronounced variations make seagrass beds unstable habitats. However, monsoon assemblages were relatively stable perhaps due to lack of excessive new recruits and a habitat shift by most species.